Characteristics of consultants who hold distinction awards in England and Wales: database analysis with particular reference to sex and ethnicity (BMJ Publishing Group, 2004)

(untitled)
Objective To determine whether women, ethnic minorities, and particular specialties are discriminated against in the receipt of NHS distinction awards. Design Analysis of database of consultants eligible for distinction awards. Setting England and Wales, 2002. Main outcome measures Holding of B, A, and Aplus distinction awards, analysed for all awards, irrespective of when made, and for awards made in the last five years studied. Results Women and doctors from ethnic minorities were substantially under-represented among award holders when no account was taken of potential confounding factors. Differences diminished after multivariate analysis, but some remained significant. For example, the adjusted odds ratio of women holding awards compared with men was 0.69 (95% confidence interval 0.59 to 0.82) for any award and 1.37 (0.86 to 2.20) for Aplus awards; the odds ratio for any award for non-white doctors trained abroad compared with white doctors trained in the United Kingdom was 0.45 (0.37 to 0.56). In the last five years studied the adjusted ratio of women to men was 0.94 (0.79 to 1.10) for B awards and 1.54 (0.85 to 2.83) for Aplus awards. The adjusted ratio for non-white British trained consultants was 0.86 (0.62 to 1.17) for B awards and 1.20 (0.37 to 3.87) for Aplus awards; for non-white consultants trained abroad it was 0.68 (0.54 to 0.85) for B awards and 0.69 (0.15 to 3.10) for Aplus awards; and for white consultants trained abroad it was 0.70 (0.54 to 0.91) for B awards and 0.90 (0.38 to 2.15) for Aplus awards. Conclusion Historical under-representation in award holding by women and doctors from ethnic minorities was partly explained by time spent as a consultant. Recent awards showed no under-representation of women and no appreciable under-representation of ethnic minorities overall. However, doctors who trained abroad—both white and non-white—remained under-represented for B awards.